Reatividade de anticorpos IgE, IgG1 e IgG4 a frações glicopeptídicas de Dermatophagoides pteronyssinus em indivíduos alérgicos e não alérgicos - Resende, Rafael de Oliveira (2009)
House dust mites as Dermatophagoides pteronyssinus (Dp) are considered important allergen sources for sensitization of genetically predisposed subjects. Several allergens are commonly constituted by glycoconjugates that may have affinity with lectins, such as Concanavalin A (ConA). The aim of this study was to evaluate IgE, IgG1 and IgG4 reactivity to ConA-related components from Dp extract in allergic and non-allergic subjects. ConA-bound and ConA-unbound components were obtained from Dp crude extract after fractionation on ConA-Sepharose affinity chromatography and all extracts were evaluated by ELISA and immunoblotting for detection of IgE, IgG1, and IgG4 in sera from 95 mite-sensitized patients (DP+)and 92 non-allergic (NA) subjects. In DP+ patients, IgE and IgG1 seropositivity to crude Dp extract was higher (100% and 84,2%, respectively) than to ConA-related extracts, while IgG4 seropositivity was higher to ConA-bound Dp (83,2%) as compared to other Dp extracts. Interestingly, IgG4 seropositivity to ConA-related Dp extracts, especially ConA-bound Dp, was higher in DP+ than NA subjects. Inhibition ELISA for all antibody isotypes showed a high (>80%) cross-reactivity between crude Dp and ConA-related extracts or D. farinae extract (>70%). However, partial inhibition for IgG1 (67%) and IgG4 (33%), but not for IgE, was found when using Blomia tropicalis extract. Immunoblotting revealed immunodominant bands recognized by IgE (14 and 25 kDa) and IgG4 (25 and 88 kDa) mostly in crude Dp and ConAunbound extracts, whereas IgG1 recognized bands above 78 kDa mainly in crude Dp extract. ConA-bound and ConA-unbound Dp extracts demonstrate high crossreactivity and are constituted by components that are able to induce IgE synthesis in allergic patients, and IgG1 and IgG4 in allergic and non allergic subjects.